Sie sind auf Seite 1von 3

# MATH1131 Semester 2 2016 Final Exam

Question 2(iv)

Chesta Wu
June 5, 2018

## (a) From the definition of derivative, we have

Z x+h
0 1
g (x) = lim f (u)(x + h − u) du
h→0 h 0
Z x 
− f (u)(x − u) du . (1)
0

Since
Z x+h Z x+h Z x+h
f (u)(x + h − u) du = f (u)(x − u) du + f (u)(h) du
0 0 0
Z x Z x+h
= f (u)(x − u) du + f (u)(x − u) du
0 x
Z x+h
+ f (u)(h) du , (2)
0
Rx
we may substitute (2) into (1) and eliminate 0
f (u)(x − u) du to get
!!
Z x+h Z x+h
1
g 0 (x) = lim f (u)(x − u) du + f (u)(h) du
h→0 h x 0
! !
Z x+h Z x+h
1
= lim f (u)(x − u) du + lim f (u) du
h→0 h x h→0 0
!
Z x+h Z x
1
= lim f (u)(x − u) du + f (u) du .
h→0 h x 0
!
Z h Z x
1
= lim − vf (v + x) dv + f (u) du , (3)
h→0 h 0 0

where v = u − x.

1
Since f is continuous, f maps the compact inteval S = [x − 1, x + 1] to
a compact inteval T ⊂ R for all x, h ∈ R. Therefore there exists a real
number M > 0 such that f |S is bounded by M , i.e.

|f (x)| < M

for all x ∈ S.
Hence, taking |h| < 1, we have
Z Z
h h
vf (v + x) dv ≤ |v||f (v + x)| dv

0 0
Z h
≤M |v|dv
0
2
M |h|
= . (4)
2
1
Multiply both sides of (4) by hand taking the limit h → 0, we get
!
1 h
Z
lim vf (v + x) dv = 0 (5)
h→0 h 0

## by the squeeze/sandwich/pinching theorem.

Substitute (5) into (3) and get
Z x
g 0 (x) = f (u) du .
0

## By the fundamental theorem of calculus, we also have

Z x
0
h (x) = f (t) dt
Z0 x
= f (u) du
0
= g 0 (x)

as was to be shown.
(b) g(0) = h(0) = 0

2
(c) We integrate the equation for g by parts to get
Z x  Z u 
d
g(x) = (x − u) f (t) dt du
0 du 0
 Z u x Z x Z u  
d
= (x − u) f (t) dt − f (t) dt (x − u) du
0 0 0 du
Z x Z u u=0
=0− f (t) dt (−1) du
0 0
Z x Z u 
= f (t) dt du
0 0
= h(x)